Determinación del índice potencial interpretativo de los sitios de excursionismo del cantón Pangua, provincia de Cotopaxi. - Caiza Caiza, Katia Elizabeth (2023)
The present research work was carried out in the Pangua canton, Cotopaxi Province. The general objective was to determine the index of the interpretive potential (IPI) of the resources of the hiking sites in Pangua. The first objective was to identify the hiking sites for the tourism stakeholders. The second objective was to determine the index of the interpretive potential of the resources of the defined sites, through georeferencing, direct observation, and application of field cards. The last objective was to design public use strategies for the sites with the greatest interpretive potential for sustainable use. This research has a qualitative and descriptive approach; therefore, interviews, surveys, direct observation, data collection, and IPI index evaluation sheets were applied. As expected, results, the snowball technique was used to proceed with the mapping of actors in the area of tourism, in this case, the parish autonomous decentralized governments, the tourism directorate of Pangua, where interviews were conducted at strategic sites. There were 6 hiking sites identified, and each one of these is evaluated and justified with the nine criteria of Morales and Lozano, it is worth mentioning that the evaluation was conducted in the defined sites, which determined the IPI, inventory, physical conditions of these and georeferencing, giving the score of 27.5 in the Ruta de la Caña with a range of 0. 62 having a (IPI) High, followed by the 7 Cascadas del Zapanal with 27.9 with a range of 0.63 which also obtained the High score, these two are the ones that obtained the highest score of the 4 sites. Finally, the analytical method was used with the SWOT analysis technique, the internal external matrix was implemented where the sum of the strengths and weaknesses and opportunities and threats was made. A weighted score of 3.76 (MEFI) and 3.01 (MEFE) was obtained for the Pangua canton. With these scores obtained the strategies were proposed which are. Develop strategic plans to position the canton of Pangua as a tourist destination. Motivate visitors to visit the canton's hiking sites through the use of social networks, web pages, etc. As a general conclusion, 6 hiking sites were identified, they were evaluated to know IPI and to know if they have interpretive features as a recommendation we have, in the identified hiking sites to carry out adventure activities that make an impression and have a reception of foreign and domes.